Bimbingan Teknis Identifikasi Permasalahan dan Alternatif Strategi Pengembangan Pakan Sapi Pedaging melalui Focus Group Discussion di Kabupaten Kolaka Timur - Abadi, Musram; Nafiu, La Ode; Nasiu, Firman; Yunus, Lukman; Gandri, La; Gerhana, Gerhana; Safitri, Safitri (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2026)
Feed plays a key role in the livestock production system. As is known, feed contributes up to 60–70% of the total production costs in beef cattle farming. This activity aims to identify problems and alternative strategies for beef cattle feed availability through FGDs in East Kolaka Regency which were held on August 12, 2025. The activity was implemented in the form of Focus Group Discussions (FGDs) with relevant stakeholders, such as breeders, extension workers, government officials, academics, and business actors. The material for this community service activity is the identification of problems, potential, and alternative strategies for beef cattle feed availability. The stages of implementation of this community service were carried out in several stages, namely (a) the first stage, preparation and (b) the second stage, implementation. The results obtained indicate that the FGD on beef cattle feed availability in East Kolaka Regency identified the main problems in the form of dependence on fluctuating natural feed, low livestock skills, and limited facilities and institutions. On the other hand, there is great potential in the form of grazing land, agricultural by-products, a supportive climate, and support from regional policies. Therefore, the local government provides adequate policy and budget support, while encouraging livestock farmers to be more active in utilizing local resources. This strategy is expected to address the challenge of providing sustainable feed and increase the productivity of beef cattle farms in East Kolaka Regency.